2021
DOI: 10.21608/agro.2021.53113.1243
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Some Soil Amendments on Improving Growth, Productivity and Quality of Soybean Grown under Different Irrigation Intervals

Abstract: E GYPT is currently experiencing water shortage, which causes a threat to crop productivity and efficiency of water use, especially in light of the current climatic changes. A field experiment was done to study effect of irrigation intervals (12, 16 and 20 days), soil amendments (compost, biochar, polyacrylamide "PAM" and hydrogel) beside control and their interaction on root, morpho-physiological, yield and quality traits of soybean.1-Prolonging irrigation intervals up to 20 days significantly decreased root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Furthermore, the grain yield was a more important factor for estimating the crude protein yield than the grain protein content (Figure 4a). The positive effect of irrigation on the grain protein accumulation determined in the present study (Table 3) was previously reported by many authors [11,14,[19][20][21]31]. However, in this research, the protein content and crude protein yield increases were not always in a linear relationship with the amount of available water.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the grain yield was a more important factor for estimating the crude protein yield than the grain protein content (Figure 4a). The positive effect of irrigation on the grain protein accumulation determined in the present study (Table 3) was previously reported by many authors [11,14,[19][20][21]31]. However, in this research, the protein content and crude protein yield increases were not always in a linear relationship with the amount of available water.…”
Section: Discussionsupporting
confidence: 78%
“…The maximum values for water use efficiency WUE were recorded for plots irrigated at 35% of ASM followed with significant differences by that irrigated at 50% of ASM (El-Karamity, 1998). Ali and Abdel Aal (2021) found significantly decreased in leaf area, plant height and dry matter plant -1 , pods plant -1 , no. and weight of seeds pod -1 , 100-seed weight and seed yield plant -1 and fed -1.…”
Section: Introductionmentioning
confidence: 85%